Application of tellurate-based glass material in X-ray detection
By using tellurate glass material to prepare an X-ray detector structure, the problems of weak absorption capacity and preparation complexity of existing materials are solved, and X-ray imaging with high sensitivity and low detection limits are achieved, with the advantages of controllable shape and large-area preparation.
Patent Information
- Application Number
- CN202510425871.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-08-15
AI Technical Summary
The existing semiconductor X-ray detector materials have problems such as weak high-energy X-ray absorption capacity, complex preparation process, high cost and poor stability, and the application of traditional glass materials in X-ray detectors has not been reported.
An X-ray detector with a semiconductor detector structure is prepared by using tellurite-based glass material as the detection dielectric layer, combining the gold positive electrode and the negative electrode layer, and an electrode is made through sputtering to achieve large-area plasticized image formation.
It realizes X-ray imaging with high sensitivity, low detection limit and high stability, reduces the difficulty and cost of preparation, has controllable shape and large-area preparation capabilities, and is safe and environmentally friendly.
Smart Images

Figure CN120500153A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of X-ray detection, and in particular relates to an application of a tellurite-based glass material in X-ray detection. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.
[0003] X-ray detectors have gained attention due to their applications in security inspections, medical diagnostics, industrial nondestructive testing, scientific research, and space exploration. Semiconductor-based direct X-ray detection offers higher spatial resolution and simpler system configuration than scintillation detection. Consequently, direct X-ray detectors and materials have attracted increasing attention in recent years. High sensitivity and low detection limits are crucial for reducing the risks of ionizing radiation in nondestructive medical diagnostics. Currently, X-ray detectors based on conventional semiconductor materials, such as α-Se, Si, HgI2, and polycrystalline Cd(Zn)Te, dominate the market. However, the weak absorption of high-energy X-rays by α-Se and Si hinders their application. Similarly, HgI2 X-ray detectors suffer from high leakage current and poor stability. Cd(Zn)Te crystals show great potential for room-temperature X-ray detection, but they suffer from disadvantages such as uneven charge transport and high noise, as well as complex preparation processes and high manufacturing costs, which pose challenges for practical application. Furthermore, imaging detectors based on these conventional materials are primarily single-pixel. Due to their low cost and unique optoelectronic properties, interest in perovskites for high-energy X-ray detection is rapidly increasing. However, most halide perovskites contain the element Pb and exhibit environmental instability, which limits their application. Therefore, lead-free detection materials have excellent comprehensive properties such as low cost, easy large-scale preparation, high X-ray absorption coefficient, high resistivity, and long life.
[0004] Glass is widely used in optical, electrical, and thermal fields due to its unique short-range ordered structure. Its unique characteristics include controllable shape, large-area fabrication, simple preparation processes, and flexible composition adjustment. However, to the inventors' knowledge, there are currently no reports of glass being used in semiconductor detector structures for X-ray detectors. Summary of the Invention
[0005] In order to address the shortcomings of the existing technology, the purpose of the present invention is to provide an application of a tellurite-based glass material in X-ray detection. The present invention directly uses the glass material to prepare an X-ray detector with a semiconductor detector structure, which can achieve clear X-ray imaging and has the advantages of simple preparation process, low cost, safety and environmental protection.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] In a first aspect, a tellurite-based glass material is used in the preparation of an X-ray detector or an X-ray detector. The X-ray detector or the X-ray detector used in the X-ray detector is a semiconductor detector structure, including a detection medium layer and a positive electrode and a negative electrode arranged on opposite sides of the detection medium layer. The material of the detection medium layer is the tellurite-based glass material, and the tellurite-based glass material is a glass material having a molar percentage of TeO2 of not less than 25%.
[0008] Researchers have discovered that using tellurite-based glass materials can replace semiconductor materials in the fabrication of semiconductor-based X-ray detectors, enabling X-ray detection. Tellurite-based glass materials offer controllable shapes, large-area fabrication capabilities, and streamlined fabrication processes, thereby reducing the operational complexity, fabrication process complexity, and cost of semiconductor-based X-ray detectors.
[0009] In some embodiments, the molar percentage of TeO 2 in the tellurite-based glass material is 25 to 90%.
[0010] In some embodiments, the tellurite-based glass material further includes one or more of Ga2O3, MoO3, WO3, BaO, Li2CO3, Cs2CO3, B2O3, TiO2, CdO2, Yb2O3, La2O3..., but the tellurite glass is not limited to the listed oxides and the listed components.
[0011] In a second aspect, an X-ray detector is provided, which is a semiconductor detector structure and includes a detection medium layer, wherein a positive electrode layer and a negative electrode layer are respectively provided on two opposite sides of the detection medium layer; the material of the detection medium layer includes the tellurite-based glass material used in the above-mentioned application.
[0012] In the present invention, the tellurite glass material can be directly formed into a layered structure to serve as the detection medium layer. Alternatively, the tellurite glass material can be first formed into glass fibers, and then the glass fibers are assembled into a glass fiber array to form the detection medium layer. To secure the glass fiber array, a substrate is used to secure it.
[0013] In a third aspect, an X-ray detection imaging system includes:
[0014] An X-ray source, used for emitting X-rays toward the object to be measured;
[0015] An X-ray detector, configured to receive X-rays from an X-ray source or passing through an object to be detected, and convert the X-rays into electrical signals; the X-ray detector is the X-ray detector described in the above application;
[0016] An imaging device is used to convert the electrical signals from the X-ray detector into image information.
[0017] The X-rays emitted by the X-ray source are directed toward the X-ray detector, and the object to be detected is arranged on the path of the X-rays from the X-ray source to the X-ray detector.
[0018] In a fourth aspect, a tellurite-based glass material comprises the following components in molar fractions: 80-90 parts of TeO2, 10-20 parts of Ga2O3; or, 14 parts of BaO, 26-76 parts of TeO2, and 10-60 parts of MO3, where M is Mo or W.
[0019] Research in the present invention shows that the tellurite-based glass material composed of the above-mentioned components has the characteristics of high resistivity, low X-ray absorption coefficient, high mobility lifetime product and low dark current drift. The X-ray detector with a semiconductor detector structure prepared with this glass material has the advantages of high sensitivity, low detection limit and high stability.
[0020] In some embodiments, BaO comprises 14 parts, TeO 2 comprises 46-66 parts, and MO 3 comprises 20-40 parts. Studies have shown that the glass material under these conditions has better performance and is more conducive to the preparation of X-ray detectors.
[0021] In the present invention, the glass material has a glass transition temperature of 360-460°C. When the components are TeO2 and Ga2O3, it is TeO2-Ga2O3 glass, abbreviated as GTOG; when the components are BaO, TeO2, and MoO3, it is BaO-TeO2-MoO3 glass, abbreviated as BTMG; and when the components are BaO, TeO2, and WO3, it is BaO-TeO2-MoO3 glass, abbreviated as BTWG. The glass transition temperature of GTOG is 370-380°C, while the glass transition temperatures of BTMG and BTWG are 362-460°C. This demonstrates that the glass material provided by the present invention has high thermal stability.
[0022] In a fifth aspect, a method for preparing the above-mentioned tellurite-based glass material is provided, which comprises mixing the raw materials according to their composition, heating them to melt, mixing them uniformly, maintaining the temperature and allowing them to stand, and finally quenching and annealing the obtained material.
[0023] The preparation method of the present invention is a high-temperature quenching method, which is simple and conducive to large-area and high-quality preparation.
[0024] The beneficial effects of the present invention are:
[0025] 1. This invention utilizes tellurite-based glass materials in an X-ray detector with a semiconductor detector structure. This allows for a vertical structure for imaging detection, with the imaging object placed between the X-ray source and the glass fiber array detector. Due to the controllable shape of this glass material, its large-scale fabrication capability, and its simple manufacturing process, it can be molded into curved shapes for 3D curved surface imaging or drawn into various shapes such as fibers for array imaging. This provides a wide dynamic range, meeting the imaging requirements of objects at various latitudes.
[0026] 2. When the present invention applies tellurite-based glass materials to X-ray detectors with semiconductor detector structures, positive and negative electrodes can be produced on the upper and lower surfaces by sputtering, thereby completing the preparation of X-ray detectors based on the glass material, effectively improving carrier mobility performance, simplifying the device manufacturing process, and reducing costs.
[0027] 3. The tellurite-based glass material provided by the present invention has advantages such as high resistivity, high X-ray absorption coefficient, high mobility lifetime product and low dark current drift. Therefore, the X-ray detector obtained based on this glass material has the advantages of high sensitivity, ultra-low detection limit and extremely high stability.
[0028] 4. The tellurite-based glass material provided by the present invention is easy to prepare on a large scale with high quality, has low cost, high glass transition temperature, is not easy to deliquesce, has stable physical and chemical properties, does not contain toxic elements, and is safe and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0030] Figure 1 Optical photographs of TeO2-Ga2O3 glass and BaO-TeO2-MoO3 (WO3) glass prepared in Examples 1-3 of the present invention, a is Example 1, b is Example 2, and c is Example 3;
[0031] Figure 2 Schematic diagram of the structure of the X-ray detector based on tellurite TeO2-Ga2O3 glass and BaO-TeO2-MoO3 (WO3) glass of the present invention, a is a schematic diagram of the structure, b is a schematic diagram of the photoelectric process of the Au / BTXG SCs / Au device of the present invention under X-ray radiation, and c is the photoconductive gain;
[0032] Figure 3is the X-ray absorption coefficient of the TeO2-Ga2O3 glass and the BaO-TeO2-MoO3 (WO3) glass prepared in Examples 1-3 of the present invention, a is the X-ray absorption coefficient of the TeO2-Ga2O3 glass, and b is the X-ray absorption coefficient of the BaO-TeO2-MoO3 (WO3) glass;
[0033] Figure 4 The resistances of the TeO2-Ga2O3 glass and the BaO-TeO2-MoO3 (WO3) glass prepared in Examples 1-3 of the present invention, a is the resistance of the TeO2-Ga2O3 glass, and b is the resistance of the BaO-TeO2-MoO3 (WO3) glass;
[0034] Figure 5 is the carrier mobility lifetime product of the TeO2-Ga2O3 glass and the BaO-TeO2-MoO3 (WO3) glass prepared in Examples 1-3 of the present invention, a is the carrier mobility lifetime product of the TeO2-Ga2O3 glass, and b is the carrier mobility lifetime product of the BaO-TeO2-MoO3 (WO3) glass;
[0035] Figure 6 The photocurrent curves of the X-ray detectors based on tellurite TeO2-Ga2O3 glass and BaO-TeO2-MoO3 (WO3) glass prepared in Examples 1-3 of the present invention at different doses are shown in Figures a and b, respectively, as shown in Figures 1 and 3.
[0036] Figure 7 These are sensitivity test graphs of X-ray detectors based on tellurite TeO2-Ga2O3 glass and BaO-TeO2-MoO3 (WO3) glass prepared in Examples 1-3 of the present invention. a is a sensitivity test graph of the X-ray detector based on TeO2-Ga2O3 glass, and b is a sensitivity test graph of the X-ray detector based on BaO-TeO2-MoO3 (WO3) glass.
[0037] Figure 8 Detection limit test graphs of X-ray detectors based on tellurite TeO2-Ga2O3 glass and BaO-TeO2-MoO3 (WO3) glass prepared in Examples 1-3 of the present invention: a is a detection limit test graph of the X-ray detector based on TeO2-Ga2O3 glass, and b is a detection limit test graph of the X-ray detector based on BaO-TeO2-MoO3 (WO3) glass;
[0038] Figure 9Dark current drift curves of the X-ray detectors based on tellurite TeO2-Ga2O3 glass and BaO-TeO2-MoO3 (WO3) glass prepared in Examples 1-3 of the present invention, a is the dark current drift curve of the X-ray detector using TeO2-Ga2O3 glass, and b is the dark current drift curve of the X-ray detector using BaO-TeO2-MoO3 (WO3) glass;
[0039] Figure 10 This is a structural schematic diagram of the 3D curved surface X-ray detection and imaging based on tellurite TeO2-Ga2O3 glass in the present invention. a is an implementation diagram of the CT imager, b is a schematic diagram of the X-ray imaging system of the GTOG curved array X-ray detector, c is a planar array X-ray detector, d is a photo of the curved GTOG X-ray detector array, e is the curved GTOG X-ray detector and the imaged object, f is X-ray imaging of an "8"-shaped object of the curved GTOG X-ray detector under 40keV soft X-rays and 600V voltage, g is a photo of the planar GTOG X-ray detector array, h is the planar GTOG X-ray detector and the imaging object, and i is a comparison diagram of X-ray imaging of an "8"-shaped object of the planar GTOG X-ray detector under 40keV soft X-rays and an applied voltage of 600V.
[0040] Figure 11 Schematic diagram of the assembly process and imaging performance of the BaO-TeO2-MoO3 tellurite glass fiber array detector of the present invention. Figure a shows the preparation and assembly of the glass fiber; b and c are photographs of the glass fiber; d is a photograph of a cured single-layer glass fiber, showing a 10×10 pixel array consisting of 100 sheets; e is the dark current of the glass fiber array detector; f is the photocurrent of the glass fiber array detector; g is an X-ray image with a dose rate of 7.42 μGy / s. -1 (40keV), electric field 5000V cm -1 . DETAILED DESCRIPTION
[0041] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs.
[0042] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof.
[0043] Since glass is not directly used in semiconductor detector structure X-ray detectors in the prior art, it is difficult to give full play to the advantages of glass materials. Therefore, the present invention proposes an application of tellurite-based glass materials in X-ray detection.
[0044] A typical embodiment of the present invention provides an application of a tellurite-based glass material in the preparation of an X-ray detector or X-ray detection. The X-ray detector or X-ray detection uses a semiconductor detector structure, including a detection medium layer and a positive electrode and a negative electrode arranged on opposite sides of the detection medium layer. The material of the detection medium layer is the tellurite-based glass material, and the tellurite-based glass material is a glass material having a molar percentage of TeO2 of not less than 25%.
[0045] In some embodiments, the molar percentage of TeO 2 in the tellurite-based glass material is 25-90%.
[0046] In some embodiments, the tellurite-based glass material further includes one or more of Ga2O3, MoO3, WO3, BaO, Li2CO3, Cs2CO3, B2O3, TiO2, CdO2, Yb2O3, La2O3..., but the tellurite glass is not limited to the listed oxides and components.
[0047] Another embodiment of the present invention provides an X-ray detector having a semiconductor detector structure, including a detection medium layer, wherein a positive electrode layer and a negative electrode layer are respectively provided on two opposite sides of the detection medium layer; the material of the detection medium layer includes the tellurite-based glass material used in the above-mentioned application.
[0048] In some embodiments, the positive electrode layer is formed by sputtering.
[0049] In some embodiments, the negative electrode layer is formed by sputtering.
[0050] In some embodiments, the thickness of the positive electrode layer is 80-120 nm, preferably 98-102 nm.
[0051] In some embodiments, the thickness of the negative electrode layer is 80-120 nm, preferably 98-102 nm.
[0052] In some embodiments, the thickness of the detection medium layer is 1-3 mm, preferably 1.5-2.5 mm.
[0053] In some embodiments, the material of the positive electrode layer is gold (Au).
[0054] In some embodiments, the negative electrode layer is made of gold (Au).
[0055] Studies have shown that when the electrode material is Au, the performance of the tellurite-based glass material provided by the present invention can be better utilized.
[0056] Specifically, the preparation steps are as follows:
[0057] An ion sputtering device is used to sputter gold as a positive electrode layer on the top surface of the tellurite-based glass, and an ion sputtering device is used to sputter gold as a negative electrode layer on the bottom surface of the tellurite-based glass to obtain a tellurite-based glass X-ray detector.
[0058] A third embodiment of the present invention provides an X-ray detection imaging system, comprising:
[0059] An X-ray source, used for emitting X-rays toward the object to be measured;
[0060] An X-ray detector, configured to receive X-rays from an X-ray source or passing through an object to be detected, and convert the X-rays into electrical signals; the X-ray detector is the X-ray detector described in the above application;
[0061] An imaging device is used to convert the electrical signals from the X-ray detector into image information.
[0062] Wherein, the imaging device may be a computer.
[0063] A fourth embodiment of the present invention provides a tellurite-based glass material comprising the following components in molar fractions: 80-90 parts TeO2, 10-20 parts Ga2O3; or 14 parts BaO, 26-76 parts TeO2, and 10-60 parts MO3, where M is Mo or W.
[0064] In the present invention, the total molar fraction of TeO2 and Ga2O3 is 100 parts; the total molar fraction of BaO, TeO2 and MO3 is 100 parts.
[0065] In some embodiments, TeO2 comprises 85.50-86.00 parts and Ga2O3 comprises 14.00-14.50 parts, more specifically, TeO2 comprises 85.70-85.75 parts and Ga2O3 comprises 14.25-14.30 parts.
[0066] In some embodiments, BaO is 14 parts, TeO 2 is 46-66 parts, and MO 3 is 20-40 parts.
[0067] In some embodiments, BaO is 14 parts, TeO2 is 57.5-58.5 parts, and MO3 is 27.5-28.5 parts.
[0068] In some embodiments, the glass material has a glass transition temperature of 360-460° C. Specifically, when the components include TeO2 and Ga2O3, the glass transition temperature of the glass material is 370-380° C.; when the components include BaO, TeO2, and MO3, the glass transition temperature of the glass material is 362-460° C.
[0069] A fifth embodiment of the present invention provides a method for preparing the above-mentioned tellurite-based glass material, comprising mixing the raw materials according to their composition, heating them to melt, mixing them evenly, maintaining the temperature and allowing them to stand, and finally quenching and annealing the resulting material.
[0070] In some embodiments, the melting temperature is 800-850°C. This condition ensures that all raw materials are melted. Specifically, the raw materials are melted and allowed to stand in a platinum crucible. More specifically, the mixing method after melting is stirring. The stirring speed is preferably 50-70 rpm, and the stirring time is preferably 20-30 hours. Under these conditions, the raw materials are uniformly mixed. Stirring and standing can clarify the glass material liquid, thereby ensuring the performance of the glass material.
[0071] In some embodiments, the standing time is 8-12 hours. The effect is better under this condition.
[0072] In some embodiments, the annealing temperature is 350-450° C. Specifically, the annealing time is 45-55 hours.
[0073] More specifically, different glass preparation methods are as follows:
[0074] The raw materials Ga2O3 and TeO2 are mixed in corresponding proportions; the temperature is raised to 800-850°C until the raw materials are in a molten state, and the liquid is stirred to mix evenly, and then allowed to stand at 800-850°C; finally, after quenching and annealing, TeO2-Ga2O3 glass with excellent X-ray detection performance is obtained.
[0075] The raw materials BaCO3, TeO2, and MoO3 are mixed in corresponding proportions; the temperature is raised to 800-850°C until the raw materials are in a molten state, and the liquid is stirred to mix evenly, and then allowed to stand at 800-850°C; finally, after quenching and annealing, BaO-TeO2-MoO3 glass with excellent X-ray detection performance is obtained.
[0076] The raw materials BaCO3, TeO2, and WO3 are mixed in corresponding proportions; the temperature is raised to 800-850°C until the raw materials are in a molten state, and the liquid is stirred to mix evenly, and then allowed to stand at 800-850°C; finally, after quenching and annealing, BaO-TeO2-WO3 glass with excellent X-ray detection performance is obtained.
[0077] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0078] Unless otherwise specified, the raw materials used in the examples are commercially available; the methods used are all based on existing technologies unless otherwise specified.
[0079] Example 1
[0080] An X-ray detector based on tellurite TeO2-Ga2O3 glass comprises, arranged from bottom to top, a gold cathode layer, TeO2-Ga2O3 glass, and a gold cathode layer. The cathode layer is 100 nm thick. The cathode layer is 100 nm thick. The cathode layer and the cathode layer are disposed on the lower (6 mm × 6 mm) and upper (6 mm × 6 mm) surfaces of the TeO2-Ga2O3 glass, respectively. The TeO2-Ga2O3 glass is a rectangular parallelepiped, 6 mm long, 6 mm wide, and 2 mm high.
[0081] The preparation method of TeO2-Ga2O3 glass comprises the following steps:
[0082] First, mix the raw materials Ga2O3 and TeO2 with the following molar percentage composition: TeO2 85.71%, Ga2O3 14.28%, and put them into a platinum crucible. Place the platinum crucible in a temperature-controlled resistance wire furnace, raise the temperature to 800°C, and burn the raw materials to a molten state. Then, in order to ensure that the solution is fully mixed, immerse the platinum stirring paddle in the solution, set the stirring program to 60rpm, and the stirring time is 24h. After the stirring is completed, remove the stirring paddle from the solution, and let the solution stand at 800°C for 10h. Then remove the platinum crucible from the furnace and quench it to obtain TeO2-Ga2O3 glass. In order to eliminate the thermal stress inside the glass, the glass is annealed at 360°C for 48h to obtain a light yellow, uniform, transparent, streak-free and bubble-free TeO2-Ga2O3 glass (such as Figure 1 After orientation, a glass sheet with a length of 6 mm, a width of 6 mm, and a height of 2 mm is produced. Figure 1 The above preparation processes were all carried out in air.
[0083] The method for preparing the above-mentioned TeO2-Ga2O3 glass-based X-ray detector comprises the following steps:
[0084] Gold was sputtered on the top surface of TeO2-Ga2O3 glass as the positive electrode layer using an ion sputtering instrument, and gold was sputtered on the bottom surface of TeO2-Ga2O3 glass as the negative electrode layer using an ion sputtering instrument to obtain an X-ray detector based on TeO2-Ga2O3 glass. The structure is shown in the figure below. Figure 2 As shown in a.
[0085] The above-mentioned method for preparing 3D curved surface X-ray detection imaging based on TeO2-Ga2O3 glass comprises the following steps:
[0086] First, a mold was used to shape the TeO2-Ga2O3 glass into an arc shape. In addition, a 10×14 array was created for the curved glass. That is, a 14×10 mask was used. An ion sputtering instrument was used to sputter gold as a positive electrode layer on the top surface of the TeO2-Ga2O3 glass, and an ion sputtering instrument was used to sputter gold as a negative electrode layer on the bottom surface of the TeO2-Ga2O3 glass to evaluate its X-ray imaging capability ( Figure 10 d) Use metal probes to connect the upper and lower positive and negative electrodes, and select a tungsten anode X-ray tube as the X-ray source. The X-ray energy can be adjusted within the range of 40-150keV. Based on the calibrated radiation dose rate, different X-ray dose rates can be obtained by changing the tube voltage and current. Figure 10 As shown in Figure b, the object used for imaging is an "8" square grid measuring 10 mm x 6 mm, which is bent into an arc with a curvature comparable to that of GTOG. The object is then placed on a homemade platform. Imaging is performed under X-ray irradiation with a photoelectron energy of 40 keV and an applied voltage of 600 V, as shown in Figure 2. Figure 10 f, the results show that the curved array X-ray detector finally produces a clear image shape with no distortion of the square grid pattern. At the same time, the schematic diagram of the planar array X-ray detector and its imaging system is shown in Figure 10 c. The imaging diagram of the planar array x-ray detector is shown in Figure 10 As shown in Figure 1, the image edges are distorted, and the shape deviates from the actual object. This discrepancy is due to the different distances between the curved object and the flat detector. This further demonstrates the uniqueness and authenticity of curved detectors in achieving 3D X-ray imaging.
[0087] Example 2
[0088] An X-ray detector based on tellurite BaO-TeO2-MoO3 glass comprises, arranged from bottom to top, a gold cathode layer, the BaO-TeO2-MoO3 glass, and a gold cathode layer. The cathode layer is 100 nm thick. The positive layer is 100 nm thick. The cathode and positive layers are respectively arranged on the lower (6 mm × 6 mm) and upper (6 mm × 6 mm) surfaces of the BaO-TeO2-MoO3 glass. The BaO-TeO2-MoO3 glass is a rectangular parallelepiped with a length of 6 mm, a width of 6 mm, and a height of 2 mm.
[0089] The preparation method of BaO-TeO2-MoO3 glass comprises the following steps:
[0090] First, mix the raw materials BaCO3, TeO2, and MoO3 in a molar percentage composition: BaO 14%, TeO2 58%, MoO3 28%, and put them into a platinum crucible. Place the platinum crucible in a temperature-controlled resistance wire furnace and heat it to 800°C to burn the raw materials to a molten state. Then, in order to ensure that the solution is fully mixed, immerse the platinum stirring paddle in the solution, set the stirring program to 60rpm, and the stirring time is 24h. After the stirring is completed, remove the stirring paddle from the solution and let the solution stand at 800°C for 10h. Then remove the platinum crucible from the furnace and quench it to obtain BaO-TeO2-MoO3 glass. In order to eliminate the thermal stress inside the glass, the glass is annealed at 350°C for 48h to obtain a yellowish-brown, uniform, transparent, streak-free and bubble-free BaO-TeO2-MoO3 glass (such as Figure 2 After orientation, a glass sheet with a length of 6 mm, a width of 6 mm, and a height of 2 mm is produced. Figure 1 The above preparation processes were all carried out in air.
[0091] The method for preparing the X-ray detector based on BaO-TeO2-MoO3 glass comprises the following steps:
[0092] An X-ray detector based on BaO-TeO2-MoO3 glass was obtained by sputtering gold on the top surface of BaO-TeO2-MoO3 glass as the positive electrode layer and sputtering gold on the bottom surface of BaO-TeO2-MoO3 glass as the negative electrode layer using an ion sputtering instrument. Figure 2 As shown in a.
[0093] The preparation method of the BaO-TeO2-MoO3 glass-based fiber array X-ray detection imaging comprises the following steps:
[0094] The glass fiber adopts the strategy of "melting and stretching in a platinum crucible" and then annealing. The diameter and length of the fiber can be achieved by controlling the stretching parameters. The diameter and length of the fiber can be achieved by controlling the stretching parameters. In the experiment, optical fibers with diameters between 150 and 950 μm can be obtained. The annealing treatment eliminates the internal stress of the glass fiber and reduces the brittleness of the glass fiber. According to the experimental results of large glass blocks, an annealing process was designed. Considering that the glass transition temperature of BaO-TeO2-MoO3 glass is 362°C, the specific annealing procedure is: first heat the glass to 350°C at a rate of 10°C / h, then anneal at 350°C for 48h, and finally cool to room temperature at a rate of 10°C / h. A radiation detection imaging array was manufactured using this glass fiber. Using epoxy resin as the matrix, 10 glass fibers were first assembled into a single layer, and finally the layers were successfully assembled into a 10×10 pixel BaO-TeO2-MoO3 glass fiber array detector. As Figure 11d, where the glass fibers are evenly arranged. An imaging object is placed between the X-ray source and the glass fiber array detector to complete the X-ray imaging demonstration experiment. The imaging part is shown in Figure 11 The preparation of the array detector eliminates the signal interference caused by the serial phenomenon between adjacent pixels, which is more conducive to improving the clarity and effectiveness of imaging.
[0095] Example 3
[0096] An X-ray detector based on tellurite BaO-TeO2-WO3 glass comprises, arranged from bottom to top, a gold cathode layer, the BaO-TeO2-WO3 glass, and a gold cathode layer. The cathode layer is 100 nm thick. The positive layer is 100 nm thick. The cathode and positive layers are respectively arranged on the lower (6 mm × 6 mm) and upper (6 mm × 6 mm) surfaces of the BaO-TeO2-WO3 glass. The BaO-TeO2-WO3 glass is a rectangular parallelepiped, 6 mm long, 6 mm wide, and 2 mm high.
[0097] The preparation method of BaO-TeO2-WO3 glass comprises the following steps:
[0098] First, mix the raw materials BaCO3, TeO2, and WO3 in a molar percentage composition: BaO 14%, TeO2 58%, WO3 28%, and put them into a platinum crucible. Place the platinum crucible in a temperature-controlled resistance wire furnace and heat it to 850°C to burn the raw materials to a molten state. Then, in order to ensure that the solution is fully mixed, immerse the platinum stirring paddle in the solution, set the stirring program to 60rpm, and the stirring time is 24h. After the stirring is completed, remove the stirring paddle from the solution and let the solution stand at 850°C for 10h. Then remove the platinum crucible from the furnace and quench it to obtain BaO-TeO2-WO3 glass. In order to eliminate the thermal stress inside the glass, the glass is annealed at 400°C for 48h to obtain a yellowish-brown, uniform, transparent, streak-free and bubble-free BaO-TeO2-WO3 glass (such as Figure 1 c). After orientation, a glass sheet with a length of 6 mm, a width of 6 mm, and a height of 2 mm is processed. Figure 2 The above preparation processes were all carried out in air.
[0099] The method for preparing the X-ray detector based on BaO-TeO2-WO3 glass comprises the following steps:
[0100] An ion sputtering instrument was used to sputter gold on the top surface of BaO-TeO2-WO3 glass as the positive electrode layer, and an ion sputtering instrument was used to sputter gold on the bottom surface of BaO-TeO2-WO3 glass as the negative electrode layer to obtain an X-ray detector based on BaO-TeO2-WO3 glass. The structure is shown in the figure below. Figure 2 As shown in a.
[0101] Test Example 1
[0102] The TeO2-Ga2O3 glass prepared in Example 1 and the BaO-TeO2-MoO3 (WO3) glass prepared in Examples 2-3, as well as α-Se, β-Ga2O3, Cd 0.9 Zn 0.1 The X-ray absorption coefficients of Te and MAPbBr3 were theoretically calculated using the photon cross section database. The X-ray absorption coefficient is related to the elements contained in the compound, but has nothing to do with the preparation method and structure. The theoretical calculation results are as follows: Figure 3 As shown. Figure 3 It can be seen that the X-ray absorption coefficient of TeO2-Ga2O3 glass and BaO-TeO2-MoO3 (WO3) glass is significantly higher than that of α-Se and β-Ga2O3 in the energy range of 30-120keV, and lower than that of Cd 0.9 Zn 0.1 Te.
[0103] The resistance of the TeO2-Ga2O3 glass prepared in Example 1 and the BaO-TeO2-MoO3 (WO3) glass prepared in Examples 2-3 was obtained by testing the IV curve. The test results are as follows: Figure 4 As shown by Figure 4 It can be seen that the resistivity of TeO2-Ga2O3 glass is 3.24×10 14 Ωcm, the resistivity of BaO-TeO2-MoO3 glass is 2.42×10 14 Ωcm, the resistivity of BaO-TeO2-WO3 glass is 3.08×10 14 Ωcm.
[0104] The carrier mobility lifetime product of the TeO2-Ga2O3 glass prepared in Example 1 and the BaO-TeO2-MoO3 (WO3) glass prepared in Examples 2-3 was obtained by testing the photocurrent data. The test results are as follows: Figure 5 As shown by Figure 5 It can be seen that the carrier mobility lifetime product of TeO2-Ga2O3 glass is 1.093×10 -2 cm 2 V -1 The carrier mobility lifetime product of BaO-TeO2-MoO3(WO3) glass is 5.02×10 -3 cm 2 V -1 , The carrier mobility lifetime product of BaO-TeO2-WO3 glass is 7.22×10 -3 cm 2 V -1 .
[0105] The photocurrent of the TeO2-Ga2O3 glass X-ray detector prepared in Example 1 and the BaO-TeO2-MoO3 (WO3) glass X-ray detector prepared in Examples 2-3 at different doses was tested by continuously increasing the applied X-ray tube current to increase the X-ray dose. The test results are shown in FIG. Figure 6 As shown by Figure 6 It can be seen that by increasing the X-ray dose rate, the photocurrent of the X-ray detector continues to increase.
[0106] The sensitivity of the TeO2-Ga2O3 glass X-ray detector prepared in Example 1 and the BaO-TeO2-MoO3 (WO3) glass X-ray detector prepared in Examples 2-3 under X-ray energy was tested. Figure 6 The data is fitted with current density and dose rate, and the fitting results are as follows Figure 7 As shown, the sensitivity of the TeO2-Ga2O3 glass X-ray detector is 321.47μC Gy air -1 cm -2 The sensitivity of the BaO-TeO2-MoO3 glass X-ray detector is 239μC Gy air -1 cm -2 The sensitivity of the BaO-TeO2-WO3 glass X-ray detector is 287μC Gy air -1 cm -2 .
[0107] The detection line of the TeO2-Ga2O3 glass X-ray detector prepared in Example 1 and the BaO-TeO2-MoO3 (WO3) glass X-ray detector prepared in Examples 2-3 is the dose rate when the signal-to-noise ratio is 3. The test results are as follows Figure 8 As shown, the minimum detection limit of the TeO2-Ga2O3 glass X-ray detector is 8.579nGy air s -1 The minimum detection limit of the BaO-TeO2-MoO3 glass X-ray detector is 5.70nGy air s -1 The minimum detection limit of the BaO-TeO2-WO3 glass X-ray detector is 7.30nGy air s -1
[0108] The dark current drift curves of the TeO2-Ga2O3 glass prepared in Example 1 and the BaO-TeO2-MoO3 (WO3) glass X-ray detectors prepared in Examples 2-3 were tested. The dark current of the X-ray detectors was measured within 1000s and finally calculated. Figure 9 As shown, the dark current drift of the TeO2-Ga2O3 glass X-ray detector is 1.96×10 -7 nA cm - 1 s -1 V -1 The dark current drift of the BaO-TeO2-MoO3 glass X-ray detector is 4.47×10 -8 nA cm -1 s -1 V -1 The dark current drift of the BaO-TeO2-WO3 glass X-ray detector is 3.05×10 -8 nA cm -1 s -1 V -1 .
[0109] X-ray radiation dose is calibrated using an X-ray detector. Different X-ray doses can be generated by adjusting the high-voltage generator's tube voltage and current. Table 1 shows the relationship between photocurrent and X-ray dose rate when the high-voltage generator's tube voltage is 40 keV. The data in Table 1 demonstrates that as the high-voltage generator's photocurrent increases, the generated X-ray dose rate also increases.
[0110] Table 1. Relationship between photocurrent and dose rate at 40keV X-ray energy
[0111]
[0112] The 3D curved surface X-ray detection imaging of the TeO2-Ga2O3 glass prepared in Example 1 is tested. The schematic diagram of the curved array X-ray detector and its imaging system is shown in FIG. Figure 10 As shown in Figure 2(b), the object used for photography is an "8" square grid with a size of 10mm × 6mm, which is bent into an arc with a curvature comparable to that of GTOG. The object is then placed on a self-made platform. The imaging part is shown in Figure 2(c). Figure 10 As shown in f. Figure 10 f is an image obtained under X-ray irradiation with a photoelectron energy of 40 keV and an applied voltage of 600 V. Obviously, the curved array X-ray detector ultimately produces a clear image shape with no distortion of the square grid pattern.
[0113] The fiber array X-ray detection imaging of the BaO-TeO2-MoO3 glass prepared in Test Example 2 is as follows: Figure 11 d, where the glass fibers are evenly arranged. An imaging object is placed between the X-ray source and the glass fiber array detector to complete the X-ray imaging demonstration experiment. Figure 11 d and 11e are 10 × 10 pixel BTM glass fiber array detectors at 1000 V cm -1The imaging results of the glass fiber array strongly demonstrate the potential of glass fiber array devices in the field of X-ray detection imaging ( Figure 11 g).
[0114] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A use of a tellurite-based glass material in the preparation of an X-ray detector or an X-ray detector, wherein the X-ray detector or X-ray detector employs a semiconductor detector structure comprising a detection dielectric layer and a positive electrode and a negative electrode disposed on opposite sides of the detection dielectric layer, wherein the detection dielectric layer is made of the tellurite-based glass material, wherein the tellurite-based glass material has a molar percentage of TeO2 of not less than 25%.
2. The use according to claim 1, characterized in that: In the tellurite-based glass material, the molar percentage of TeO2 is 25-90%.
3. The use according to claim 1, characterized in that: The tellurite-based glass material also includes one or more of Ga2O3, MoO3, WO3, BaO, Li2CO3, Cs2CO3, B2O3, TiO2, CdO2, Yb2O3, and La2O3.
4. An X-ray detector, characterized in that: Its structure is a semiconductor detector structure, including a detection medium layer, and a positive electrode layer and a negative electrode layer are respectively provided on two opposite sides of the detection medium layer; the material of the detection medium layer includes the tellurite-based glass material used in the application described in any one of claims 1 to 3.
5. The X-ray detector according to claim 4, wherein: The positive electrode layer is made by sputtering; Alternatively, the negative electrode layer is formed by sputtering; Alternatively, the thickness of the positive electrode layer is 80-120 nm, preferably 98-102 nm; Alternatively, the thickness of the negative electrode layer is 80-120 nm, preferably 98-102 nm; Alternatively, the thickness of the detection medium layer is 1-3 mm, preferably 1.5-2.5 mm; Alternatively, the material of the positive electrode layer is gold; Alternatively, the negative electrode layer is made of gold.
6. An X-ray detection imaging system, characterized in that: include: An X-ray source, used for emitting X-rays toward the object to be measured; An X-ray detector is used to receive X-rays from an X-ray source or passing through an object to be detected and convert the X-rays into electrical signals; The X-ray detector is the X-ray detector described in any one of claims 1 to 3 or the X-ray detector described in claim 4 or 5; An imaging device is used to convert the electrical signals from the X-ray detector into image information.
7. A tellurite-based glass material, characterized in that: The invention comprises the following components in molar proportions: 80-90 parts of TeO2, 10-20 parts of Ga2O3; or 14 parts of BaO, 26-76 parts of TeO2, and 10-60 parts of MO3, where M is Mo or W.
8. The tellurite-based glass material according to claim 1, wherein: The sum of the molar fractions of TeO2 and Ga2O3 is 100 parts; and / or the sum of the molar fractions of BaO, TeO2 and MO3 is 100 parts; Or, TeO285.50-86.00 parts, Ga2O314.00-14.50 parts; or, TeO285.70-85.75 parts, Ga2O314.25-14.30 parts; Or, BaO 14 parts, TeO2 46-66 parts, MO 320-40 parts; Or, BaO 14 parts, TeO2 57.5-58.5 parts, MO3 27.5-28.5 parts; Alternatively, the glass transition temperature of the glass material is 360-460°C; specifically, when the components are TeO2 and Ga2O3, the glass transition temperature of the glass material is 370-380°C; when the components are BaO, TeO2 and MO3, the glass transition temperature of the glass material is 362-460°C.
9. A method for preparing the tellurite-based glass material according to claim 7, characterized in that: The raw materials are mixed according to the composition, heated until melted, mixed evenly, kept at the temperature and allowed to stand, and finally quenched and annealed to obtain the product.
10. The preparation method according to claim 9, characterized in that: Melting temperature is 800-850℃; Or, the standing time is 8-12h; Alternatively, the annealing temperature is 350-450°C.